Mechanisms of formation of hybrid immunity in people who recovered from COVID-19 and were vaccinated with SARS-CoV-2 peptide antigens - L. P. Sizyakina; I. I. Andrreeva; M. V. Kharitonova; N. S. Zaitseva; D. S. Lyubimov; V. Ya. Zakurskaya; Areg A. Totolian (Медицинская иммунология)
The relevance of the current epidemic situation of a new coronavirus infection is determined by new strains of the virus and the registration of cases of re-infection in COVID-19 survivors earlier. In this regard, the questions about the expediency and nature of vaccination of those who have been ill attract close attention, moreover it has affected the formation of the concept of “hybrid immunity”. The aim of this study was to analyze changes in the parameters of the immune system, reflecting their regulatory and functional potential, in response to the introduction of the peptide vaccine EpiVacCorona to persons who have suffered from the new coronavirus infection. To study the features of the formation of hybrid immunity, a retrospective analysis of the observation of 43 study participants was carried out. The inclusion criteria were data confirming COVID-19 in mild and moderate forms of the course in the period from six months to a year ago, a low level or absence of antibodies to the nucleocapsid protein SARS-CoV-2, a negative PCR result for the presence of the SARS-CoV-2 virus, the absence of comorbid pathology. The subpopulation composition, regulatory and functional potential of the immune system were determined by flow cytofluorimetry using a set of monoclonal antibodies corresponding to the goals. 21 days after the administration of a single dose of EpiVacCorona, antibodies to the vaccine peptide antigens were registered in all study participants at the highest coefficient of positivity values for the SARS-CoV-2-IgG-Vector test system used. In addition, there was a fourfold increase in the number of specific IgG to the N protein. A specific immune response to recombinant SARS-CoV-2 antigens was accompanied by a decrease in the circulation of the number of monocytes expressing TLR4, T helper cells expressing the interaction coreceptor with antigen-presenting cells, unconnected B memory with an increase in the number of B lymphocytes expressing the CD40 T-B coreceptor interaction molecule. The remaining differences in the functioning of the immune system identified in patients with COVID-19 before the vaccination in comparison with the control data have not changed. The differences consist in a decrease in the proportion of monocytes expressing HLA-DR, an increase in the expression of interaction molecules on T and B lymphocytes, an increase in the number of Treg, B1 cells, activated B lymphocytes with a decrease in the proportion of suppressor Breg and B memory. The totality of the presented data demonstrates that the COVID-19 infection that preceded vaccination in mild and moderate clinical course contributes to the formation of immunological memory, which made it possible to form a secondary immune response even to a single injection of peptide antigens of the virus.